The Application of Hand Massage for Pain Management in Post-Laparotomy Patient; A Case Study - Fitria, Dellia Ayu; Hakam, Mulia (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2025)
Post-laparotomy pain is one of the major problems in nursing practice frequently experienced by patients after undergoing surgical procedures. Poorly managed pain can lead to discomfort, sleep disturbances, increased physiological stress, limited mobility, and delayed wound healing. Effective pain management is an essential part of enhancing patient comfort and accelerating recovery. In addition to pharmacological approaches, several studies showed that non-pharmacological interventions such as hand massage can serve as effective, safe, and easily applicable pain management. This study aims to identify patient’s outcome after receiving hand massage therapy using baby oil in reducing pain in post-laparotomy. The research design employed a descriptive quantitative case study approach. The subject was a single post-laparotomy patient at dr. Soebandi Hospital, Jember, experiencing moderate pain, as measured by the Numeric Rating Scale (NRS). The patient was given nursing care, and one of the interventions was hand massage, as well as pain relief medication. The hand massage intervention was administered twice daily for four consecutive days, with each session lasting 10 minutes. The patient's pain scale was observed daily. The results of the case study showed a decrease in pain from a scale of 6 on the first day to a scale of 3 on the fourth day Patient said that everytime he got pain medication, he still feel the pain, but the massage made it better. Therefore, this therapy can be considered as an effective therapy and applicable complementary nursing intervention in managing post-laparotomy pain